Design and development of DSP-based hybrid controller for servo driver applications - Bulale I., Yusuf; Salami, Momoh Jimoh Eyiomika; Sulaiman, Marizan (2003)
A hybrid system involving the conventional proportional-integral-derivative (PID) controller and fuzzy-logic system for servo drivers needed in many motion control applications is examined in this paper. The importance of this approach is the tuning of PID eontroller using fuzzy logic system, which by so doing enhances the performance of conventional PID controller in terms of settling time, percentage overshoot and steady-state-error. Thus, this proposed system is meant to compensate for the poor performance of the PID controller as a result of various factors such as unknown nonlinearities, time delays, disturbances as well as changes in system parameters. The second part of this work is the implementation of the hybrid controller using digital signal processor (DSP) as this offers high speed, number crunching capability and the ability to produce a good accurate tracking with minimum time delay for many industrial applications such as power inverters, motion controllers, semiconductor packaging, computer disk drives, packaging assembly, high speed, high precise motion of material transfer and automotive control applications where some of these applications may require a fast and high precision processing. Both simulation results and hardware implementation of the proposed controller have shown the feasibility of this approach as it produces fast response and smooth motion control.